2020
DOI: 10.1001/jamanetworkopen.2020.4714
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Prenatal Exposure to Alcohol and Tobacco and Neonatal Brain Activity

Abstract: IMPORTANCE Research to date has not determined a safe level of alcohol or tobacco use during pregnancy. Electroencephalography (EEG) is a noninvasive measure of cortical function that has previously been used to examine effects of in utero exposures and associations with neurodevelopment. OBJECTIVE To examine the association of prenatal exposure to alcohol (PAE) and tobacco smoking (PTE) with brain activity in newborns.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

4
6

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 56 publications
1
24
0
Order By: Relevance
“…Several studies have reported associations of smoking and drinking during pregnancy with negative gestational outcomes and health in offspring ( Schoendorf and Kiely, 1992 ; Scragg et al, 1993 ; Cnattingius, 2004 ; Mamluk et al, 2017 ; Shuffrey et al, 2020 ). Although these reports clearly demonstrate there are adverse effects of PAE and PTE, they do not provide information about the contributions of timing and amount of exposure on fetal ANS function.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported associations of smoking and drinking during pregnancy with negative gestational outcomes and health in offspring ( Schoendorf and Kiely, 1992 ; Scragg et al, 1993 ; Cnattingius, 2004 ; Mamluk et al, 2017 ; Shuffrey et al, 2020 ). Although these reports clearly demonstrate there are adverse effects of PAE and PTE, they do not provide information about the contributions of timing and amount of exposure on fetal ANS function.…”
Section: Discussionmentioning
confidence: 99%
“…31,32 Facial abnormalities characteristic of fetal alcohol spectrum disorder can be observed for low levels of alcohol use if exposure occurs when neural crest cells are migrating to form facial structures, 33 and changes in neonatal brain activity are observed with low levels of prenatal alcohol exposure. 34 Alternatively, imprecision or bias in reporting the amount of alcohol consumed may obscure a dosedependent effect. Because alcohol use during pregnancy is stigmatized, information about the amount consumed may be more vulnerable to reporting biases than responses about mere presence or absence of exposure.…”
Section: Risk Of Spontaneous Abortion By Gestational Week With Alcohol Exposure (N[5353)mentioning
confidence: 99%
“…The authors claim that the outcomes of their study may suggest the abnormal maturation of cortical networks. Overall, the findings showed that any level of prenatal tobacco exposure has an association with new-born brain activity [ 26 ]. Additionally to this, a study measuring prenatal tobacco exposure on 239 children aged 8 uncovered an association between pregnancy-time cotinine, a nicotine metabolite, level and executive functions evaluated via the Behaviour Rating Inventory of Executive Function.…”
Section: Resultsmentioning
confidence: 99%